Coordinating health promotion in a federal state over the course of 30 years: a case report from Switzerland - Thomas Mattig (Tabriz University of Medical Sciences, 2019)
In a federal state such as Switzerland, the 26 cantons enjoy wide autonomy in all policy areas, including health policy. In the late 1980s, after the signing of the Ottawa Charter for health promotion, the Swiss Confederation and the cantons decided to create a foundation whose goal it was to initiate, coordinate and evaluate health promotion and disease prevention activities throughout the country. Thirty years later, the many stakeholders in the field have accepted health Promotion Switzerland as a key actor. The foundation was able to successfully initiate and coordinate projects in such priority areas as "Healthy Body Weight," "Mental Health -Stress" and "Strengthening Health Promotion & Prevention." But several challenges remain, for example, chronic noncommunicable diseases, an aging population, mental disorders, prevention in healthcare-challenges the foundation will have to face and to which it is expected to provide solutions.